Quality, Importance, and Instruction: The Perspectives of Teachers of Students with Visual Impairments on Graphics Use by Students. (January 2014) - Zebehazy, Kim T.; Wilton, Adam P.
Introduction: This study investigated the perceptions and practices of teachers of students with visual impairments in Canada and the United States regarding graphics (both tactile and print) that are used by students with visual impairments. Questions focused on quality, importance, and instruction in the use of graphics. Methods: An electronic survey was disseminated. Results were summarized by percentage, based on the number of respondents who answered each question. Parallel questions that compared responses for tactile versus print graphics were statistically compared using the Wilcoxon signed-rank test, and effect sizes were computed. Results: In general, teachers valued the use of graphics and the need to provide instruction. Significant differences were found in how teachers answered tactile and print graphic questions. Fewer than 50% of the respondents felt that graphics were appropriately adapted on large-scale assessments, that there was sufficient instruction in the use of graphics in mainstream classrooms, or that there was an adequate amount of instructional time to teach the use of graphics. Discussion: Findings highlighted a need to gain insight into effective teaching strategies that help students gather information from both tactile and print graphics. Attention to students with low vision using print graphics needs to be part of future investigations. Implications for practitioners: Advocacy for sufficient instruction time for graphics and continued monitoring of the quality and effectiveness of graphics in educational materials are important. Providing feedback to material producers can help to support quality. Increasing student independence and exposure to graphics could support the effective use of graphics on assessments.